Exploring the key performance indicators of green supply chain management in agro-industry. (11th February 2019) - Gardas, Bhaskar; Raut, Rakesh; Jagtap, Annasaheb H.; Narkhede, Balkrishna
Abstract : Purpose: The issue of food security is one of the critical global challenges. The Government and the industries have begun apprehending the importance of green supply chain management (GSCM) implementation in their supply chains. There are various drivers or performance indicators (PIs) of GSCM in the agro-sector. This paper aims to analyse 14 PIs using an interpretive structural modelling (ISM) approach. Design/methodology/approach: In this study, the PIs of GSCM were identified through a literature survey and opinions of field experts. The identified 14 PIs were modelled by applying an ISM methodology for establishing the interrelationship between the PIs and to identify the PIs having high influential power. Findings: The result of the investigation underlined that three PIs, namely, environmental management (PI 1), regulatory pressure (PI 3) and competitive pressure (PI 2) are the significant PIs having high driving power. Research limitations/implications: The experts' judgments were used for the development of the structural model, which could be biased influencing the reliability of the model. Also, only 14 significant PIs were considered for the analysis. This research is intended to help the policymakers, managers and supply chain designers in the food industry and in agribusiness in formulating the policies and strategies for achieving food security, conservation of the environmental resources and for improving the financial performance of the industry. Originality/value: It is pioneering research focusing on the analysis of the PIs towards the implementation of GSCM in the Indian agro-industries context using an ISM approach. This research adds value to the existing knowledge base by identifying the crucial PIs, exploring their mutual relationship and highlighting their level of influence in the case sector.